Pengaruh Struktur Modal, Profitabilitas dan Likuiditas terhadap Kebijakan Inisiasi Dividen pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI) - Rahmiati, Rahmiati; Ramadona, Suci (Jurnal Kajian Manajemen Bisnis, 2013)
This research purposes are to analyze the influece of capital structure, profitability, and likuidity to initial dividend policy on corporation which listed on Indonesian stock exchance. This research is including to causative reseach. Research sampel chosen by purposive sampling method so sample of the research is 43 corporations. The kind of data is secondary data from www.idx.co.id, www.e-bursa,com, Indonesian Capital Market Directory (ICMD). Analysis method is double linier regresion. Hypothesis test uses t statistic test. Research finding indicate that only profitability that have positive impact and significant to initial dividend policy (dividend payout ratio).